PENGARUH PENGGUNAAN APLIKASI PERDAGANGAN ELEKTRONIK TERHADAP PENDAPATAN MAHASISWA - Dananti, Kristyana; Nany, Magdalena; Zakius, Zakius (LPPM UNISDA, 2024)
Many developments in supporting technology such as online payments and electronic money increasingly support the development of electronic commerce. The ease of online business where sales can be made anywhere and anytime certainly supports student efforts to earn income, manage expenses and make investments. This research method uses a quantitative approach. The population of this study is all students in the city of Surakarta who use electronic commerce applications. The dependent variables in the study are income, expenditure and investment. While the independent variable in this study is electronic commerce. The source of data used in this study is primary data obtained from questionnaires on the Likert scale 4.Data will be analyzed by multivariate regression analysis. Electronic commerce applications have a significant effect on the amount of student income and the amount of student expenditure. However, electronic trading applications have no effect on investment activities.